Media Alternatif Tepung Terigu Tinggi Protein Untuk Pertumbuhan Jamur Escherichia coli - Anas Fadli Wijaya; Rian Anggia Destiawan (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2020)
Escherichia coli infection is caused by contaminated food and drinking water, or direct contact with someone who is sick or with animals carrying the bacteria. Diagnosis of diseases caused by E. coli can be done in several ways, but in general it is done clinically, then strengthened by microscopic examination and culture. Commercial media that is often used for culturing bacteria is Nutrient Agar (NA). NA media is a synthetic medium with a high content of carbohydrates and proteins that support bacterial growth. One ingredient that has a high content of protein and carbohydrates is high-protein wheat flour. The purpose of this study was to determine the potential of high-protein wheat flour as an alternative medium for the growth of E. coli bacteria. This study was a laboratory experimental study using the post test control group design only method using 16 replications and 2 treatments, namely NA medium as a control and high protein wheat flour as an alternative medium. The results showed that the average number of E. coli growth on NA media was 336.5 colonies while on alternative high-protein wheat flour media it was 15.19 colonies. The value of p = 0.000 with a 2-way significance level (α = 0.05) then p <α. So there is a significant difference between the number of E. coli bacteria colonies in NA media and alternative high protein wheat flour media. Alternative medium for high-protein wheat flour takes a very long time to grow E. coli bacteria so it is not maximally used as an alternative medium for the growth of E. coli.